A Topik Lingkungan dalam Pembelajaran Biologi: Telaah Sistematis Artikel Jurnal Nasional Terindeks Sinta - Sang Putu Kaler Surata; Anak Agung Inten Paraniti; Ni Wayan Ekayanti (BIOEDUSCIENCE, 2021)
Background: Biology and the environment have very close interactions in the form of biodiversity, biosphere and ecosystems. The study was systematically conducted on research results articles with the aim of identifying environmental topics in biological education, outlining the research characteristics of biological education and synthesizing research trends and gaps on environmental topics in biological education in Indonesia. Method: Cross-sectional study design is conducted through a survey of research articles published in national journals. Results: The results of a meta-analysis of the structure and content of 41 articles in the indexed journal Sinta 1-3, found environmental pollution was the most discussed topic followed by several other topics such as biodiversity, ecosystems and conservation. Conclusion: Most research uses experimental design and development research with structured instruments to obtain measurable learning outcomes. Therefore, it is necessary to diversify biological education research to focus more on meaningful learning transformation through the integration of biological education in other fields, especially bioculture diversity.